P16-specific DNA methylation by engineered zinc finger methyltransferase inactivates gene transcription and promotes cancer metastasis - Cui, Chenghua (Genome Biol, 2015)
BACKGROUND: P16 DNA methylation is well known to be the most frequent event in cancer development. It has been reported that genetic inactivation of P16 drives cancer growth and metastasis, however, whether P16 DNA methylation is truly a driver in cancer metastasis remains unknown. RESULTS: A P16-specific DNA methyltransferase (P16-dnmt) expression vector is designed using a P16 promoter-specific engineered zinc finger protein fused with the catalytic domain of dnmt3a. P16-dnmt transfection significantly decreases P16 promoter activity, induces complete methylation of P16 CpG islands, and inactivates P16 transcription in the HEK293T cell line. The P16-Dnmt coding fragment is integrated into an expression controllable vector and used to induce P16-specific DNA methylation in GES-1 and BGC823 cell lines. Transwell assays show enhanced migration and invasion of these cancer cells following P16-specific DNA methylation. Such effects are not observed in the P16 mutant A549 cell line. These results are confirmed using an experimental mouse pneumonic metastasis model. Moreover, enforced overexpression of P16 in these cells reverses the migration phenotype. Increased levels of RB phosphorylation and NFκB subunit P65 expression are also seen following P16-specific methylation and might further contribute to cancer metastasis. CONCLUSION: P16 methylation could directly inactivate gene transcription and drive cancer metastasis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13059-015-0819-6) contains supplementary material, which is available to authorized users.